Flexible Polyaniline/Poly(methyl methacrylate) Composite Fibers via Electrospinning and In Situ Polymerization for Ammonia Gas Sensing and Strain Sensing. (21st December 2016) - Jia, Xian-Sheng; Tang, Cheng-Chun; Yan, Xu; Yu, Gui-Feng; Li, Jin-Tao; Zhang, Hong-Di; Li, Jun-Jie; Gu, Chang-Zhi; Long, Yun-Ze
Abstract : Conducting polyaniline (PANI) was in situ polymerized at the surface of electrospun poly(methyl methacrylate) (PMMA) fibers to obtain flexible composite fibers. The electrical conductivity of an individual PANI/PMMA composite fiber was estimated to be 2.0 × 10 −1 S cm −1 at room temperature. The ammonia sensing properties of the samples were tested by impedance analysis. The PANI/PMMA fibers could obviously respond to low concentration of ammonia at ppb level and could respond to relatively high concentration of ammonia at 10 ppm level quickly. In addition, the sensitivity exhibited a good linear relationship to the ammonia concentration. Particularly, the flexible PANI/PMMA fibers showed a reversible change in electrical resistance with repeated cycles of bending and relaxing, and the electrical resistance decreased with the increase of curvature. These results indicate that the flexible PANI/PMMA composite fibers may be used in toxic ammonia gas detection, strain sensing, and flexible electronic devices.